2022
DOI: 10.3390/f13030385
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and Bacterial Communities in Tuber melanosporum Plantations from Northern Spain

Abstract: Tuber melanosporum (Ascomycota, Pezizales) is an ectomycorrhizal fungus that produces highly appreciated hypogeous fruiting bodies called black truffles. The aim of this paper was to research the composition of ectomycorrhiza-associated fungal and bacterial communities in T. melanosporum oak plantations. Results of this paper showed the competitive effect of T. melanosporum on other fungal species, especially other mycorrhizal and pathogenic species. T. melanosporum was shown to be associated mainly with bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…In detail, significant promotion was detected using the M2 formulation based on Pseudomonas sp. Recently, a comprehensive study of the microbiomes in truffle orchards showed that the Pseudomonas and Bradyrhizobium genera, which are known as “helper” bacteria, were present in high numbers [ 43 , 44 ]. Previous works indicated that these bacteria are able to promote root mycorrhization [ 36 ] and play a key role in establishing plant–fungal symbiosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, significant promotion was detected using the M2 formulation based on Pseudomonas sp. Recently, a comprehensive study of the microbiomes in truffle orchards showed that the Pseudomonas and Bradyrhizobium genera, which are known as “helper” bacteria, were present in high numbers [ 43 , 44 ]. Previous works indicated that these bacteria are able to promote root mycorrhization [ 36 ] and play a key role in establishing plant–fungal symbiosis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that are symbiotic with truffles are understudied, and their biological and biomedical potential has not been described. Several studies on the composition of truffle-associated microbial communities have assessed truffles collected in European countries (Vahdatzadeh et al 2019;Monaco et al 2020;Siebyła andSzyp-Borowska 2022;Herero de Aza et al 2022). However, in Russia, studies on this topic are now being reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhization helper bacteria (MHB) are widespread around the roots of different plant–fungal mycorrhizae. Past literature has suggested that Agrobacterium [ 28 ], Burkholderia [ 29 ], Pseudomonas [ 30 ], Bacillus [ 31 ], Paenibacillus [ 32 ], and the actinomycete Streptomyces [ 33 ] are mycorrhization helper bacteria. In our findings, the mycorrhizal rhizosphere exhibited a lower Simpson index and higher Shannon and ACE indices ( Table 1 ), which indicated that this area possessed higher soil bacterial diversity and evenness.…”
Section: Discussionmentioning
confidence: 99%